An investigation on factors of intention to use e-learning: a case study of Malaysian public sector personnel / Rooslaili Kamis - Kamis, Rooslaili (2013)
This study is aimed to investigate the factors that contribute to the intention to use e-learning among the Malaysian Public Sector personnel. The study was used the e-learning system named Public Sector E-Learning System (EPSA®) as a case study. Nine constructs has been determined in a research model which formulated from the various theories and models including E-Learning Success Model, Technology Acceptance Model (TAM), Theory of Reasoned Action, Theory of Planned Behavior and self-efficacy theory. From the research model, five constructs are examined as the factors that contribute to the intention to use e-learning. The five factors are computer anxiety, computer self-efficacy, system quality, content quality and learner interface design. Apart from that, perceived usefulness, perceived ease of use, attitude towards e-learning and behavioral intention to use e-learning also been investigated in this study. Data from 530 respondents was collected using a questionnaire which has been tested by reliability test as to measure the validity of the research instrument. A descriptive analysis was used to analyze the demographic characteristic of the respondents and the constructs. Furthermore, a factor analysis has been done towards the five factors as to authenticate the constructions of the factors. Based on the factor analysis results, four new component named system quality, computer self-efficacy, computer experience and computer anxiety are revealed. Thus, from this result, the research model has been revised accordingly. Hypotheses testing using correlation are conducted using these new factors in examining the relationship between the constructs. The results indicate that there was an association between the constructs. Moreover, a crosstabulation test also been conducted to the demographic factors towards the frequent use of e-learning. Additionally, a regression analysis also been conducted as to investigate the age factor towards the intention to use e-learning. One of the major findings in this study is the ease of use of the e-learning system which can be considered as the most important contributor to the intention to use e-learning. On the other hand, this finding indicates that the perceptions regarding the ease of use of the e-learning system as a key to encouraging the public sector personnel behavioral intention in making greater use of the e-learning system. With regards to this finding, system quality and computer self efficacy is considered as the significant factors in contributing to the intention to use e-learning. Furthermore, due to this finding, the stakeholder of EPSA® e-learning system should take into account the ease of use aspect into implementation of a successful e-learning system.